An Insight into Rational Drug Design: The Development of In-House Azole Compounds with Antimicrobial Activity - Daniel Ungureanu; Ovidiu Oniga; Cristina Moldovan; Ioana Ionuț; Gabriel Marc; Anca Stana; Raluca Pele; Mihaela Duma; Brîndușa Tiperciuc (Antibiotics, 2024)
Antimicrobial resistance poses a major threat to global health as the number of efficient antimicrobials decreases and the number of resistant pathogens rises. Our research group has been actively involved in the design of novel antimicrobial drugs. The blueprints of these compounds were azolic heterocycles, particularly thiazole. Starting with oxadiazolines, our research group explored, one by one, the other five-membered heterocycles, developing more or less potent compounds. An overview of this research activity conducted by our research group allowed us to observe an evolution in the methodology used (from inhibition zone diameters to minimal inhibitory concentrations and antibiofilm potential determination) correlated with the design of azole compounds based on results obtained from molecular modeling. The purpose of this review is to present the development of in-house azole compounds with antimicrobial activity, designed over the years by this research group from the departments of Pharmaceutical and Therapeutical Chemistry in Cluj-Napoca.